(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper singles out and analyzes the socio-critical aspect of the short story “Je li kriva sudbina?” (“Is Destiny to Blame?”) by the Bulgarian writer Lyuben Karavelov (1834–1879), published in Serbian. As far as Serbian literature is concerned, this represents one of the earliest critically intoned voices that draw attention to topical social transformations and, especially, emancipation of women in the mid-19th century Serbian society. Similarly, as for the subject matter, it features powerful criticism of the position and suppression of women, as well as the social model making their emancipation impossible, presenting explicitly domestic violence as a form of abuse and a mechanism of suppression. Given the fact that the author takes side with the marginalized social categories in terms of criticism, ethics and humanity, Karavelov is labeled as one of the first writers to advocate the modernization of Serbian society, in interliterary and intercultural context, and to rebel against brutality and tyranny in any social form. In addition, Karavelov can also be singled out as one of the first male writers to advocate the equality of women, condemning their suppression.